2018
DOI: 10.1250/ast.39.369
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Japanese consonant-vowel syllables in reverberation: Comparing non-native listeners with native listeners

Abstract: Long reverberation degrades the intelligibility of speech sounds. Previous studies have reported that non-native listeners have difficulty in understanding speech in reverberation more than native listeners. In the results of the previous studies, there was the possibility that lower identification scores for non-native listeners were attributed to non-native phonemes which did not exist in their native languages. The current study investigated the identification of Japanese consonant-vowel (CV) syllables in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…It is of no surprise that non-native listeners struggle more to understand speech that is not in their native language when compared to native listeners. Previous studies have found non-native listeners to perform poorer than native listeners in a range of speech perception measures, such as the ability to discriminate and identify phonetic contrasts, spoken words recognition and listening to unfamiliar and synthetic speech [1,2,3,4]. Even when a fluent non-native listener can understand speech similarly to a native listener in quiet and optimal conditions, studies have found that the non-native listener performs poorer in the acoustically adverse environments such as listening in noise [5,6,7,8,9] due to speech masking.…”
Section: Introductionmentioning
confidence: 99%
“…It is of no surprise that non-native listeners struggle more to understand speech that is not in their native language when compared to native listeners. Previous studies have found non-native listeners to perform poorer than native listeners in a range of speech perception measures, such as the ability to discriminate and identify phonetic contrasts, spoken words recognition and listening to unfamiliar and synthetic speech [1,2,3,4]. Even when a fluent non-native listener can understand speech similarly to a native listener in quiet and optimal conditions, studies have found that the non-native listener performs poorer in the acoustically adverse environments such as listening in noise [5,6,7,8,9] due to speech masking.…”
Section: Introductionmentioning
confidence: 99%